TINGKAT PENGETAHUAN DAN SIKAP IBU HAMIL TENTANG KONSUMSI TABLET FE SEBELUM DAN SESUDAH PENDIDIKAN KESEHATAN - Vica Nurdiniah; Ira Marti Ayu; Mayumi Nitami; Decy Situngkir (Jurnal Muara Sains, Teknologi, Kedokteran dan Ilmu Kesehatan, 2025)
Anaemia in pregnant women is still a problem despite the government's efforts to provide at least 90 iron tablets during pregnancy. Data from DKI Jakarta shows that the coverage of iron tablets reached 99% in 2021. Kalideres Community Health Center is one of the Community Health Centers in DKI Jakarta, and the percentage of anemia incidence among pregnant women was about 11.08%. This figure was the highest in West Jakarta. The preliminary study showed that 80% of mothers had low knowledge, and around 60% had a negative attitude towards anemia and fe tablets. Health education must be conducted to improve pregnant women's knowledge and attitude toward anemia and Fe tablets. This study used an experimental study design with a one-group pre-test and post-test design. This research was conducted from March 2023 to July 2023. The total sample consisted of 54 pregnant women in the first trimester. The sampling was using a purposive sampling technique. Data was analyzed using univariate and bivariate analysis with dependent/paired t-tests. Univariate results showed that the mean knowledge before and after health education was 3.59 and 12.65, while the mean attitude before and after health education was 39.38 and 56.56. Bivariate analysis showed a significant difference between the knowledge and attitude of pregnant women before and after health education in the Kalideres District Health Centre in 2023. To obtain the information while waiting their turn for obstetric examinations, Community health centers need to provide information exposure to pregnant women on anemia and Fe tablets using print media so that pregnant women can obtain.